Signet ring cells in carcinomatous lymphangitis due to gastric adenocarcinoma, - Beatriz da Silva Souza; Renan Rangel Bonamigo; Gabriela Lusa Viapiana; André Cartell
Abstract Cutaneous metastases are rare. They usually present as nodules or tumors. Diagnosis is based on histopathological examination and prognosis is unfavorable. This report describes the case of a female patient, 72 years old, with surgically treated gastric antrum adenocarcinoma. Pathology showed poorly differentiated adenocarcinoma with signet ring cells. It evolved with bone involvement, lymph node enlargement in the inguinal region, and skin infiltration in the lower limbs, abdomen, and root of the upper limbs. Skin biopsy demonstrated signet ring carcinoma embolizing the dermal and hypodermic vessels and invasion of adipose tissue, confirming carcinomatous lymphangitis. Carcinomatous lymphangitis is the cutaneous and subcutaneous lymphatic invasion by tumor cells. Cutaneous metastasis is relatively uncommon and presents mainly as cutaneous or subcutaneous nodules, and more rarely as inflammatory lesions. The present case reports carcinomatous lymphangitis associated with gastric cancer.